Impact of the COVID-19 confinement measures on telework in Spain - A qualitative survey - Antonio Corral; I\~nigo Isusi (European Commission, Joint Research Centre (JRC), 2020)
The spread of the COVID-19 pandemic and the associated home confinement measures in March 2020 urged many Spanish companies and their workers to "improvise" a teleworking practice for which not much previous experience was available. The qualitative survey results show that a large proportion of Spanish workers have accepted telework in relatively good terms, where a majority of them would be ready to telework more in the future if a balanced combination with physical presence at the workplace could be managed. Notwithstanding this, the research also identified some particularly conflictive issues related to conciliation (difficult to manage when all day at home), worktime (sometimes extended and problematic to stop) and occupational health, both physical (MSD related) and psychosocial (feelings of isolation).
Keywords: 330; Telework; COVID-19; Confinement; Spain; Work organisation; Job quality; Work-lifebalance